2020
DOI: 10.22159/ajpcr.2020.v13i5.37108
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Potential of Trichoderma Spp. Against Fusarium Oxysporum in Solanum Lycopersicum L.

Abstract: Objective: The main objective of this study was to determine the effect of biocontrol Trichoderma species agent against Fusarium oxysporum in Solanum lycopersicum L. Methods: Genus Trichoderma effective biocontrol agent against fungal, bacterial pathogen. The fungal isolates Trichoderma viride (Tr01), Trichoderma harzianum (Tr02), and F. oxysporum (Fu04) were also identified through morphological characterization observed under a light microscope (10x×40x). The isolates (Tr01, Tr02, Fu04) were confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The lowest fruit yield was noted in untreated plants followed by Arthrinium sp., Dermateaceae sp. Our results are in line with Ramezani (2014) who stated that application of T. harzianum biomass to the soil can effectively control the occurrence of Fusarium wilt, and ultimately promote the growth of plants with different characteristics under greenhouse conditions Similarly, Ramasamy (2020) reported that Trichoderma spp. control plant pathogen and improve yield and quality the crop.…”
Section: Effect Of Different Bioagents On Plant Growth and Disease De...supporting
confidence: 91%
“…The lowest fruit yield was noted in untreated plants followed by Arthrinium sp., Dermateaceae sp. Our results are in line with Ramezani (2014) who stated that application of T. harzianum biomass to the soil can effectively control the occurrence of Fusarium wilt, and ultimately promote the growth of plants with different characteristics under greenhouse conditions Similarly, Ramasamy (2020) reported that Trichoderma spp. control plant pathogen and improve yield and quality the crop.…”
Section: Effect Of Different Bioagents On Plant Growth and Disease De...supporting
confidence: 91%